PROFILE OF DOOMSCROLLING AMONG JUNIOR HIGH SCHOOL STUDENTS AND ITS IMPLICATIONS FOR GUIDANCE AND COUNSELING SERVICES - Faza Zahra Wulan Rajbina; Yuliati Hotifah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to describe the doomscrolling profiles of junior high school students and to formulate implications for guidance and counseling services in schools. The study employed a quantitative approach using a descriptive survey method involving 462 students at SMPN 1 Malang. Data were collected using the Indonesian version of the doomscrolling scale, consisting of 15 items with a seven-point Likert scale. Data analysis was conducted through descriptive statistics, score categorization, item analysis, and reliability testing. The results indicate that students’ doomscrolling tendencies generally fall into the low category, suggesting that the behavior of repeatedly seeking out negative information has not yet become a dominant digital habit among the majority of students. Nevertheless, there are still some students with moderate to very high tendencies who require attention within guidance and counseling services. Key findings relate to the habit of checking the news feed to confirm the occurrence of bad events, a fear of social media content but difficulty looking away, and the use of social media late into the night to search for negative news. This study provides an initial mapping of doomscrolling behavior among junior high school students in Indonesia as an empirical basis for the development of guidance and counseling services based on digital literacy, self-regulation, and digital well-being. Service implications can be addressed through classroom-based guidance focused on news literacy, group guidance using self-management techniques, group counseling using the Rational Emotive Behavior Therapy (REBT) approach, and individual counseling using the Cognitive Behavioral Therapy (CBT) approach.